UPPER EYELID RECONSTRUCTION SURGERIES; COMPARISON OF OUTCOMES BETWEEN REVERSE TENZEL FLAP VERSUS CUTLER BEARD FLAP PROCEDURE - Abbasi, Sabeen; Zeeshan Kamil; Syed Muhammad Faisal; Syed Muhammad Saad; Tanweer Hassan (Journal of Ayub Medical College Abbottabad, 2021)
Background: Objective of this study was to compare Reverse Tenzel flap and Cutler Beard flap for upper eyelid defects. Methods: This interventional study was carried out at occuloplasty department of LRBT (Layton Rahamatullah Benevoloent Trust), Karachi. Patients diagnosed with upper eye lid defect between 50 and 75 years were included after ethical approval from institutional ethical review committee and briefing patients about study dynamics. The patients were randomly divided in two groups, group A in whom reverse tanzel flap was done, while in group B Cutler beard procedure was done. Main outcome measure was eyelid contour, complete lid closure and surgical procedure time. SPSS version 25.0 was used for data analysis. Results: Reverse Tenzel flap mean age 64.00±6.17 years, mean duration of surgery 33±5.78 minutes, and mean healing time 2.2±0.41 weeks. Cutler Beard flap mean age 59.60±6.26 years, mean duration of surgery 32±5.78 minutes, and mean healing time 5.7±0.8 in 3 weeks. 60% of patients were female. 30 (50%) patients each underwent Reverse Tenzel flap and Cutler Beard flap. In Reverse Tenzel flap, no complications were observed. In Cutler Beard flap, 06 (20%) patients reported mild entropion, 04 (13.3%) retraction of flap and 02 (6.7%) were found to have mild incomplete lid closure. Conclusion: Reverse Tenzel flap was superior to Cutler Beard flap as it reported no complications, being single stage surgery with early healing. Cutler-Beard flap reported mild entropion and retraction of flaps which required second surgery and delayed healing.